Influência do tipo de cimento resinoso no comportamento mecânico de uma resina nano cerâmica - Meneghetti, Daniel Eduardo (2019)
The nanoceramic resin for CAD/CAM has 80% of inorganic load in its composition, it has similarity to human dentin, and due to the polymeric elements contained, it has reduced friability. The aim of this study is to evaluate the influence of the type of resin cement on the mechanical behavior of a nanoceramic resin (Lava Ultimate, LVU). Two dual resin cements were evaluated: self-adhesive (RelyX U200, 3M) and conventional (Rely X Ultimate, 3M), in two tests, flexural strength and compressive load. For the flexural resistance test, LVU discs (n=10) were made, which received a layer of cement and were stored in distilled water, in a chamber at 37ºC for six months. After that time, the biaxial flexion test was performed according to the piston-on-three-balls method, and the data evaluated with the Mann-Whitney test (α=0.05). For the fracture load test, LVU sheets were made, which were cemented on a material similar to dentin (NEMA G10) using both types of resin cements (n=10). Before the compressive load test, both groups were subjected to mechanical aging (50 N at 2 Hz, 500,000 cycles). Data were analyzed with t test (α=0.05). There was no statistical difference between groups for flexural strength. The type of cement did not affect the fracture load and the failure mode of the specimens evaluated in the compressive load test. It is concluded that the type of resin cement has no influence on the mechanical behavior of the nanoceramic resin.